3.5-GHz four-element MIMO antenna system for 5G laptops with a large screen-to-body ratio. Issue 9 (12th June 2020) - Chen, Shu-Chuan; Wu, Meng-Kai; Chiang, Cheng-Wei; Lin, Ming-Shing
ABSTRACT: This paper proposes a 3.5-GHz four-element multi-input multi-output (MIMO) antenna system for fifth-generation (5G) laptops. The four antennas are configured into two dual-antenna units, measuring 26 × 3 × 2 mm 3 each and separated by a distance of 6 mm, the latter of which accounts for the isolation between the two units. The two antennas in each unit are located on the two sides of the same substrate and are both three-dimensional inverted-F antennas (IFAs) of the same size, but are deployed to be skew-symmetric with respect to the top edge of the display ground. With a decoupling neutralization line connecting the two antennas in the same unit, the simulated isolation between them is enhanced by up to 8 dB. Within the operating frequency band, its measured isolation exceeds 12 dB, the simulated electric field ECC (envelope correlation coefficient) is smaller than 0.15, and the measured realized radiation efficiency is more than 40%.